Co-recycling of sewage sludge and garden waste biochar: as a growing medium for landscape plant - Sheng, Han; Feng, Jiayi; Yang, Yuantong; Fasih Ullah, Haider; Peng, Weixin; Li, Xu; Long, Fengling; Wu, Daoming; Zeng, Shucai (Journal of Environmental Engineering and Landscape Management, 2023)
Urban greening produces a large amount of garden waste, and the pyrolysis of garden waste into biochar is an effective waste management technology. Biochar has a large specific surface area and soil remediation ability. However, the knowledge about the co-recycling of sewage sludge and garden waste biochar to improve the growth of Monstera deliciosa needs to be highlighted. Therefore, we conducted a pot experiment by applying Ficus altissima litter-derived biochar (FB) at rates of 0, 1.5, and 3.0% (w/w, CK, FB1.5, and FB3) in soil amended with sewage sludge at 50% (w/w), to improve the soil properties, and further analyzed the effects of FB on growth and heavy metals (HMs) uptake of landscape plant M. deliciosa. Results showed in comparison with control setups, the addition of 3% FB treatment in sewage sludge amended soil improved the soil properties and significantly increased M. deliciosa dry weight (86.75%), root: shoot ratio (73.23%), N (99.44%), P (116.13%), K (124.40%), Pb (78.81%), and Cu (159.01%) accumulation respectively. In summary, FB3 treatment achieved the best effects in promoting plant growth and soil remediation. These findings revealed that sewage sludge and garden waste biochar could be recycled as amendments for poor acid soils under restoration, a sustainable development path for urban waste disposal.